THE ROLE OF AGRICULTURAL STARTUPS IN SUPPORTING THE IMPLEMENTATION OF FOOD SECURITY POLICIES IN INDONESIA: AN OVERVIEW FROM A BUSINESS ADMINISTRATION PERSPECTIVE - Hani Damayanti Aprilia (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
Food security is one of the strategic issues in national development, especially in the midst of challenges such as population growth, climate change, land degradation, and food distribution inequality. The Indonesian government has established a range of policies to realize a resilient food system, but its success relies heavily on cross-sectoral collaboration, including the private sector and agricultural startups. This study aims to analyze the role of agricultural startups in supporting the implementation of food security policies in Indonesia, by taking a case study on Habibi Garden. The approach used is qualitative-descriptive through literature review, business model analysis, and business administration perspectives. The results show that Habibi Garden contributes significantly to three pillars of food security: (1) increasing food availability through precision agriculture technology, (2) strengthening food accessibility by empowering small and medium farmers, and (3) supporting the use of safe and quality food through data-based cultivation practices. From a business administration perspective, Habibi Garden's success reflects the principles of cross-sector collaboration, managerial efficiency, and adaptive innovation in dealing with the dynamics of the agricultural sector. This research recommends the need for synergy between the government, the business world, and the community to accelerate the transformation of sustainable and inclusive agriculture.